PENERAPAN MEDIA PEMBELAJARAN SAINS PADA ANAK USIA DINI â€MERDEKA BELAJARâ€ DI ERA BELAJAR DI RUMAH - Adnyani, Ni Wayan (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2021)
AbstractMedium learning science for early childhood is a tool for exploration and develop scientific values and ability to think logically. Reseach in designed with a qualitative approach. Thi issues to be discussedÂ  between laun (1) How was Â the process of implementing independent science learning â€œMerdeka Belajarâ€ in the early age children at home TK Werdhi Kumara Punggul. (2) Is the tone of chidren aged in the learning era humbled at kindergarten weerdi Kumara Punggul. The aim of this research is to describe learning process, describes the efforts that in the proses teacing of sains at TK Werdi Kumara Punggul. Theory used for analyzing the problem is the constructivist theory of piaget, this research was carried out from Nopember 2020 to February 2021 with research location at TK werdi Kumara Punggul, Â Abiansemal, District Badung regency. The research subjects were teachers, children aged 4-5 years which amounted to 5 children. The method used in this Â study is qualitative descriptive method. data collection techniques through observation direct Â interviews, documentation and literature study data analysis techniques Â used analysis and arranged in a description data reduction, presentation and drawing conclusions the results of the study sho the process of applying the media learning science â€œMerdeka Belajarâ€ in earli childhood diera learning at home divided into 3 stages, namely the planning, implementation and evaluation stages, with the learning method used namely telling stories, questios and answere.